Sensors Advancements in Modeling, Design Issues, Fabrication and Practical Applications - Mukhopadhyay, S.C.; Huang, R.Y.M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
Sensors are the most important component in any system and engineers in any field need to understand the fundamentals of how these components work, how to select them properly and how to integrate them into an overall system. This book has outlined the fundamentals, analytical concepts, modelling and design issues, technical details and practical applications of different types of sensors, electromagnetic, capacitive, ultrasonic, vision, Terahertz, displacement, fibre-optic and so on. The book: addresses the identification, modeling, selection, operation and integration of a wide variety of sensors, demonstrates the concepts of different sensors technology through simulation, design and real implementations, discusses the design and fabrication of high performance modern sensors technology, presents a selection of cutting-edge applications. Written by experts in their area of research, this book will be useful reference book for engineers and scientist especially the post-graduate students find this book as reference book for their research.
Electromagnetic Sensors -- Modern CMOS Hall Sensors with Integrated Magnetic Concentrators -- Commercial Magnetic Sensors (Hall and Anisotropic Magnetoresistors) -- Improving the Accuracy of Magnetic Sensors -- Modelling Electromagnetic Field Sensors -- Dielectric Characterization of Biological Tissues: Constraints Related to Ex Vivo Measurements -- Estimation of Property of Sheep Skin to Modify the Tanning Process Using Interdigital Sensors -- Fiber Optic/Optical Fibre Sensors -- Fiber Bragg Gratings Evanescent Wave Sensors: A View Back and Recent Advancements -- Optical Fibre Humidity Sensors Using Nano-films -- Overview of the OPTO-EMI-SENSE Project: Optical Fibre Sensor Network for Automotive Emission Monitoring -- Wireless Sensors -- Wireless Sensor Networks and Applications -- Wireless Sensor Network Transport Layer: State of the Art -- Sensors for Tracking and Navigation -- Real Time Tracking and Monitoring of Human Behavior in an Indoor Environment -- Dynamic VRML-Based Navigable 3D Map for Indoor Location-Aware Systems -- Ultrasonic Sensor -- Ultrasonic Sensing: Fundamentals and its Applications to Nondestructive Evaluation -- Image Sensor -- Multimodal Image Sensor Fusion Using Independent Component Analysis -- Vision Sensing -- Fast Image Capture and Vision Processing For Robotic Applications -- Sensors Based on Human Parameter -- Affection Based Multi-robot Team Work -- Displacement Sensor -- Displacement Sensor Using Magnetostrictive Wire and Decrease of its Hysteresis Error -- THZ Sensor -- Submillimeter-Wave Coherent and Incoherent Sensors for Space Applications.
Keywords: Engineering; Chemical engineering; Computers; Artificial intelligence; Control engineering; Robotics; Mechatronics; Electrical engineering; Electronics; Microelectronics; Engineering; Electronics and Microelectronics, Instrumentation; Electrical Engineering; Information Systems and Communication Service; Artificial Intelligence (incl. Robotics).; Control, Robotics, Mechatronics; Industrial Chemistry/Chemical Engineering; Electronic books